Disease‐related distress among adults with haemophilia: A qualitative study. Issue 6 (2nd October 2019) - Mattis, Shanna; Barry, Vaughn; Taylor, Natalie; Lynch, Mary Ellen; Tatum, Katharine; Whitten, Stephanie; Kempton, Christine L.
Abstract: Introduction: Distress related to disease burden has been defined and described among people with chronic diseases including diabetes and cancer. In these populations, disease‐specific distress is associated with health outcomes. Haemophilia‐related distress is less understood. Aim: To identify qualitative features of haemophilia‐related distress among affected adults to ultimately inform the creation of a measurement tool. Methods: Adults with haemophilia A or B associated with a large haemophilia treatment centre in the south‐eastern U.S. were recruited to participate in this qualitative study. Fifteen participants completed semi‐structured telephone interviews. Interviews lasted 1‐2 hours and explored experiences of distress related to various aspects of haemophilia. Interviews were audio taped, transcribed and coded using NVIVO, software for organizing, managing and analysing qualitative data. Coding was deductive and inductive, and the analysis was thematic. Results: Haemophilia‐related distress was broadly related to feelings of isolation and vulnerability which incorporated health system factors, physical functioning, caretaker roles and psychological considerations. Specific features associated with haemophilia‐related distress included lack of trust in the knowledge of haemophilia and care provided by staff in community healthcare settings, concerns about the future such as health insurance access and ageing/disability, long‐standing feelings of being different from others and feeling like an outsider, treatment burdens and fear of acute bleeds. Protective factors included supportive relationships with family, friends and haemophilia care teams through which participants received practical and emotional support. Conclusion: Features of haemophilia‐related distress were identified. Results will facilitate distress measurement and intervention efforts to reduce distress in adults with haemophilia.